Adsorption Features of Tetrahalomethanes (CX4; X = F, Cl, and Br) on β12 Borophene and Pristine Graphene Nanosheets: A Comparative DFT Study - Mahmoud A. A. Ibrahim; Amna H. M. Mahmoud; Nayra A. M. Moussa; Gamal A. H. Mekhemer; Shaban R. M. Sayed; Muhammad Naeem Ahmed; Mohamed K. Abd El-Rahman; Eslam Dabbish; Tamer Shoeib (Molecules, 2023)
The potentiality of the β12 borophene (β12) and pristine graphene (GN) nanosheets to adsorb tetrahalomethanes (CX4; X = F, Cl, and Br) were investigated using density functional theory (DFT) methods. To provide a thorough understanding of the adsorption process, tetrel (XC-X3∙∙∙β12/GN)- and halogen (X3C-X∙∙∙β12/GN)-oriented configurations were characterized at various adsorption sites. According to the energetic manifestations, the adsorption process of the CX4∙∙∙β12/GN complexes within the tetrel-oriented configuration led to more desirable negative adsorption energy (Eads) values than that within the halogen-oriented analogs. Numerically, Eads values of the CBr4∙∙∙Br1@β12 and T@GN complexes within tetrel-/halogen-oriented configurations were −12.33/−8.91 and −10.03/−6.00 kcal/mol, respectively. Frontier molecular orbital (FMO) results exhibited changes in the EHOMO, ELUMO, and Egap values of the pure β12 and GN nanosheets following the adsorption of CX4 molecules. Bader charge transfer findings outlined the electron-donating property for the CX4 molecules after adsorbing on the β12 and GN nanosheets within the two modeled configurations, except the adsorbed CBr4 molecule on the GN sheet within the tetrel-oriented configuration. Following the adsorption process, new bands and peaks were observed in the band structure and density of state (DOS) plots, respectively, with a larger number in the case of the tetrel-oriented configuration than in the halogen-oriented one. According to the solvent effect affirmations, adsorption energies of the CX4∙∙∙β12/GN complexes increased in the presence of a water medium. The results of this study will serve as a focal point for experimentalists to better comprehend the adsorption behavior of β12 and GN nanosheets toward small toxic molecules.